Fault Tolerant Control Based on Adaptive Fuzzy Global Fast Dynamic Terminal Sliding Mode for Actuators Failures in an Octorotor UAV - Abdelmoula Saggai; Samir Zeghlache; Loutfi Benyettou (My University, 2021)
This work presents a reliable fault-tolerant tracking control system (FTTCS) for actuator faults in a octorotor unmanned aerial vehicle. The proposed FTTCS is designed based on adaptive fuzzy global fast dynamic terminal sliding mode control (AFGFDTSMC) that guarantees the global asymptotic stability of a octorotor system. To mitigate the negative impacts of model uncertainties and enhance system robustness in faulty operation, an adaptive fuzzy system is incorporated into the global fast dynamic terminal sliding mode control (GFDTSMC) scheme for adaptively identifying the model uncertainties online and compensate the actuator faults effect. Lyapunov stability analysis proofs that the developed control method design maintains the stability in the closed loop dynamics of octorotor UAV in faulty operation. Simulation results show that the proposed (FTTCS) enables the octorotor to track the desired reference commands in the presence of actuator faults with satisfactory performance
Keywords: Sliding mode control, Adaptive fuzzy logic systems, Non-linear control, Octorotor.